Congenital Cleft Lip and Palate in Children: Prevalence Rate in Russia and Worldwide, Risk Factors - Nataliya A. Kasimovskaya; Evgeniya A. Shatova ("Paediatrician" Publishers LLC, 2020)
Congenital cleft lip and palate is one of the most common congenital anomalies in children. It has significant medical and social influence on the self-realization of these patients in society. This review of various researches' results from different countries and territories of the Russian Federation (according to the MEDLINE and eLIBRARY.ru databases) provides information on prevalence rate of this pathology among children of our country and worldwide. The role of medical care organization remains unknown among all the presented results of the studies about the role of risk factors of congenital cleft lip and palate development (such as: inheritance, lifestyle, environment).